PENGGUNAAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR IPA SISWA KELAS V PADA MATERI SISTEM PENCERNAAN MANUSIA DI SD - Siregar, Annisa Mei Rina; Syafrida, Lis Yulianti; Hasibuan, Azizah Putri (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to improve student learning outcomes on the human digestive system through the application of the Role Playing learning method in grade V of SD Negeri 200108/12 Padangsidimpuan. The problem faced in this study is the low learning outcomes of students in science subjects. Based on initial observations, it is known that many students have not reached the Minimum Completeness Criteria (KKM). Therefore, this research was carried out using the Role Playing learning model, which is expected to increase students' understanding of the material taught. The method used in this study is Class Action Research which is carried out in two cycles. Each cycle consists of two meetings involving active learning activities, in which students are acted out in a drama or role related to the human digestive system. The data collected included student test results, observation sheets of student and teacher activities, and reflections carried out each cycle. The results of the study showed that there was a significant increase in student learning outcomes, where the percentage of students who completed in the first cycle reached 69.23%, and in the second cycle increased to 84.61%. In addition, teacher and student activities have also increased, with the percentage of completeness of teacher activities in the second cycle reaching 100%. From these results, it can be concluded that the use of the Role Playing method is effective in improving student learning outcomes, especially in the material of the human digestive system. However, there are still some obstacles, such as time management that needs to be further improved. This study provides recommendations for the application of the Role Playing method as an alternative learning that can increase students' active participation in the learning process.